Claims against Iraqi oil and gas : legal considerations and lessons learned / Rex J. Zedalis. - Zedalis, Rex J. (Cambridge University Press, 2010)
This volume presents the first comprehensive examination of the legal issues surrounding international debt recovery on claims against Iraqi oil and gas. In addition to presenting a snapshot view of Iraq's outstanding debt obligations and an analysis of the significance of the theory of odious debt in the context of the Iraqi situation, the list of legal issues examined includes relevant provisions of the Iraqi Constitution of 2005, controlling Security Council resolutions, pertinent articles of the KRG oil and gas law (No. 22) of 2007 and the many nuanced and technical questions raised thereby, legal pronouncements aimed at protecting Iraqi oil and gas and those adopted in selected other nations, and general problems associated with recognition and enforcement of awards or judgments that may involve such oil and gas or revenues from the sale thereof. Also discussed are the lessons learned by the handling of the Iraq debt experience and the transferability of those lessons to future situations.